Deteksi Penyakit Citrus Vein Phloem Degeneration (CVPD) dengan Teknik Polymerase Chain Reaction (PCR) pada Tanaman Jeruk di Bali - MEITAYANI, NI PUTU SWARI; ADIARTAYASA, WAYAN; WIJAYA, I NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.3, No.2, April 2014)
ABSTRACTS Detection of Citrus Vein Phloem Degeneratin (CVPD) Disease by Polymerase Chain Reaction (PCR) Technique on Citrus Plant in Bali CVPD disease is one of many important disease on citrus plant caused by Liberobacter asiaticum . The mechanism of infection is not yet known, so that the efforts to control the disease have not been adequately. In the research, we tried to detect CVPD disease on citrus plant at several locations in the centre of the citrus plantation in Bali used the PCR technique. The results of reseach showed eleven from eighteen sample is positive have contain for the L. asiaticum that show size of DNA 1160 bp, because the size of 1160 bp DNA bands is expression by L. asiaticum , then the citrus leaf samples were detected positive for the L. asiaticum . Based on the results of the calculation incidence of the disease with percentage of attack is 54,38% and the intensity of CVPD diseased plants was 9,86% showed CVPD disease was spread over eight villages consist of Katung, Belancan, Bayung Gede, Awan, Catur, Pengotan, Pelaga and Petang. Keyword: Citrus Vein Phloem Degeneration (CVPD) , Liberobacter asiaticum, Polymerase Chain Reaction (PCR)
Keywords: Citrus Vein Phloem Degeneration (CVPD), Liberobacter asiaticum, Polymerase Chain Reaction (PCR)